Direct evidence for opposite effects of D-glucose and D-glyceraldehyde on cytoplasmic pH of mouse pancreatic β-cells. Issue 4 (April 1986) - Arkhammar, Per; Berggren, Per-Olof; Rorsman, Patrik
Abstract : The effects of D-glucose, D-glyceraldehyde, glibenclamide, D-600, NH4 + and high concentrations of K + on cytoplasmic pH (pH i ) were investigated in dispersed and cultured pancreatic β-cells from ob/ob mice. The cytoplasmic pH was measured with the fluorescent H + -indicator quene 1. The average pH i value in resting β-cells was 6.71. Addition of 20 m M of the physiological stimulus D-glucose increased pH i with 0.05 units. Both glibenclamide and high concentrations of K + decreased pH i . The latter effects were completely reversed by D-600, supporting the notion that free cytoplasmic Ca 2+ can be involved in the regulation of pH i . In contrast to D-glucose, 10m M of D-glyceraldehyde decreased pH i by 0.09 units, an effect persisting even in the presence of D-600. From the present study it is evident that D-glyceraldehyde and D-glucose have opposite effects on pH i in pancreatic β-cells.